Simultaneous liver kidney transplantation and (bilateral) nephrectomy through a midline is feasible and safe in polycystic disease - Jochmans, Ina; Monbaliu, Diethard; Ceulemans, Laurens J.; Pirenne, Jacques; Fronek, Jiri (PLOS ONE, 2017)
In Eurotransplant, 50% of simultaneous liver kidney transplantations (SLK) are performed for polycystic disease. Classically, liver and kidney are transplanted in two steps: liver through a subcostal incision, kidney through a separate oblique incision. Liver and kidney volume can make this ‘two-step’ procedure challenging, especially if simultaneous native nephrectomy is indicated. A ‘one-step’ SLK through a xiphopubic laparotomy might be a safe alternative, facilitating mobilization of the voluminous polycystic liver and native nephrectomy whilst offering access to iliac fossae for kidney transplantation. One-step SLK procedures for polycystic disease were introduced in 08/2013 at IKEM Prague (n = 6) and 11/2014 at University Hospitals Leuven (n = 6). Feasibility and safety of the one-step technique were investigated. We compared surgical data and outcomes obtained with the one-step technique to all consecutive two-step procedures performed for polycystic disease at the University Hospitals Leuven between 2008–2014 (n = 23). Median (interquartile range) are given. One-step SLK offered broad and adequate exposure for the hepatectomy, nephrectomies and transplantations, which were all uneventful. Morbidity, patient (100% vs 91%, p = 0.53) and graft survival (100% graft survival for liver and kidney in both groups) were comparable between one-step and two-step SLK. Liver cold ischaemia time was comparable [6.0 (4.4–7.6) vs. 7.1 (3.9–7.3), p = 0.077], kidney cold ischaemia time was shorter in one-step compared to two-step SLK [8.1 (6.4–9.3) vs. 11.7 (10.0–14.0), p<0.001)]. Total procedural time was also shorter in one-step compared to two-step SLK [6.8 (4.1–9.3) vs. 9.0 (8.7–10.1), p = 0.032], while all underwent bilateral (67%) or unilateral (33%) nephrectomy (compared to 0% and 52% in two-step SLK, respectively). In one-step SLK, 67% received a pre-emptive kidney transplant compared to 46% in two-step SLK. 5/12 two-step SLK became dialysis dependant after pre-transplant nephrectomy, the 4 dialysis-dependant patients with one-step SLK had not undergone pre-transplant nephrectomy. In conclusion, one-step SLK for polycystic disease is feasible and safe.